2013
DOI: 10.1074/jbc.m113.486654
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans Leukotoxin Utilizes a Cholesterol Recognition/Amino Acid Consensus Site for Membrane Association

Abstract: Background: A repeats-in-toxin (RTX) leukotoxin and its integrin receptor aggregate in cholesterol-rich lipid rafts. Results: The affinity of the toxin to cholesterol is driven by a cholesterol recognition/amino acid consensus (CRAC) motif. Conclusion: Leukotoxin cytotoxicity is regulated by the CRAC motif. Significance: Other RTX toxins contain this CRAC motif, suggesting a role for cholesterol recognition in RTX cytolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(122 citation statements)
references
References 77 publications
4
115
0
3
Order By: Relevance
“…There is, however, evidence that the lipid composition is important for the embedding of LtxA in the membrane. The content of cholesterol in the membrane greatly improves the membrane binding, a feature that apparently requires the cholesterol recognition/ amino acid consensus site CRAC 336 , which is conserved in other RTX toxins (60). This clearly shows that it is not only the immediate affiliation to the membrane that determines the cellular effects of the toxin.…”
mentioning
confidence: 83%
“…There is, however, evidence that the lipid composition is important for the embedding of LtxA in the membrane. The content of cholesterol in the membrane greatly improves the membrane binding, a feature that apparently requires the cholesterol recognition/ amino acid consensus site CRAC 336 , which is conserved in other RTX toxins (60). This clearly shows that it is not only the immediate affiliation to the membrane that determines the cellular effects of the toxin.…”
mentioning
confidence: 83%
“…LFA-1 clustering to lipid rafts is initiated by a LtxA-induced increase in cytosolic calcium that triggers the activation of calpain, cleavage of talin, and mobilization of LFA-1 into cholesterol and sphingolipid-rich microdomains of the plasma membrane. More recently, Brown et al [380] demonstrated that LtxA contains two cholesterol recognition/amino acid consensus (CRAC) sites, one (CRAC336) highly conserved among RTX toxins, while the second (CRAC503) is unique to LtxA. They further showed that a peptide corresponding to CRAC336 inhibited the LtxA cytotoxic activity and demonstrated that a point mutation in the CRAC336 site abolished LtxA toxicity.…”
Section: Interaction With Cell Receptors and Trafficmentioning
confidence: 94%
“…Therefore, we expected not only that this residue was not critical to CRAC site function but also that the proline substitution would also not contribute to any change in cholesterol binding. Thus, CdtB mutation of the CRAC region within CdtC (33) and with those of other investigators who made similar CRAC site mutations of residues within the CdtC subunit of Cdts produced by other bacterial species as well as to other cholesterol-binding proteins (30,31,42,50). In each instance CRAC site mutations resulted in a loss of cholesterol binding and associated downstream biological effects; in contrast, CdtB R110P had no effect on Cdt binding and CdtB internalization, confirming our expectation for the relative role of each of these residues within the CRAC site and overall role in the CdtB-cholesterol interaction.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that cholera toxin simultaneously binds with high affinity to multiple receptors as a result of receptor concentration within the raft (56,57). Likewise, the pore-forming leukotoxin from A. actinomycetemcomitans recognizes cholesterol via a CRAC site, which facilitates clustering to its receptor in the context of lipid rafts (50). Another pore-forming toxin, the aerolysin from Aeromonas hydrophila, which binds to glycosylphosphatidylinositol (GPI)-anchored proteins, also utilizes the concentrating properties of rafts to facilitate oligomerization, a requisite for channel formation (56,58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation